การจำลองข้อมูลเพื่อเปรียบเทียบความแม่นยำในการพยากรณ์ ระหว่างวิธีโครงข่ายประสาทเทียมกับวิธีซัพพอร์ตเวกเตอร์แมชชีน - นันทณัฐ พันธุ์สีดา (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This thesis attempted to identify a simulation study to compare prediction accuracy between the backpropagation artificial neural network and support vector machine. The method was to compare the forecasting accuracy using area under ROC curve (AUC) and misclassification rate (MCR). The average values of the AUC was the support vector machines with the laplacian kernel method provides better prediction performance than the backpropagation artificial neural network in most cases ,except in case independent variables was poisson distribution The average values of the MCR was that in all cases the distributions was studied in this research . Method with support vector machines with the laplacian Kernel to the error rate in the classification have the lowest . The Backpropagation Artificial Neural Network have the error rate in the highest classification in all cases.